A review on properties and applications of nano clay, silica dioxide and titanium oxide / Rahida Wati Sharudin … [et al.] - Sharudin, Rahida Wati; Mohd Azhar, Mohd Rezza Emir; Mat Shayuti, Muhammad Shafiq; Akbar, Suffiyana (Universiti Teknologi MARA, 2021)
Nanoparticles have recently been used as fillers or additives in materials for different desired applications. Due to the environmental concerns and rising of nanomaterials usages worldwide, nanoparticles have been focused in research and development. An increase in consumption is indicated by various applications of nanomaterials for both commercial and domestic applications. Nanoparticles own special physical and chemical properties which help in modifying performance of materials or final products. The characterisation of nanoparticles includes crystallographic structure, surface morphology, particles’ size and functional groups. Nano clays and metal oxides of titanium and silica are selected nanoparticles to be discussed on their properties that affect the performance of materials. Along with the studies investigating the properties of the nanoparticles, an interesting concern is to discover the changes in properties of materials when nanoparticles are being added. Properties include mechanical, thermal and physiochemical are improved due to the presence of the nanoparticles in the materials’ matrices, thus existing the applications for the food packaging, the lubricant oils and as the antimicrobial agent. This paper reviews the physical and chemical properties of nano clay, silica oxide and titanium oxide as well as the enhanced properties of materials when being filled with nanoparticles in specific applications.